MANAGEMENT OF INVESTMENT ACTIVITY IN CONDITIONS OF DECENTRALIZATION - Yemets , O.I. (The actual problems of regional economy development, 2019)
Effective investment activity of the business entity is a platform for the successful development of not only the micro level, but also the macro level. Management of investment activity is often determined by state, regional and sectoral development strategies. The pace of economic growth (GDP) is a key factor that affecs the decision of economic entities to invest. An analysis of the dynamics of the nominal GDP of Ukraine was made and trends in its growth were determined, GDP growth rates for the period from 2005 to 2018 were determined, the share of gross accumulation in the GDP structure was calculated. The analysis of this information allows us to conclude that nominal GDP has a tendency to increase, but the share of gross accumulation in GDP ranges from 14.1% to 28.2% over the analyzed period. This will make it possible to make a strategic decision on managing investment activities in a decentralized environment. Management of investment activity should be distinguished at macro and micro levels. We have found that the effectiveness of such kind of activity directly depends on the favorable investment climate and macroeconomic regulation, as well as the long-term and short-term periods of its implementation. Conditions of investment activity of the economic entity can be determined by using the next algorithm: assessment of the investment strategy; determination the most attractive ways of profitable capital investments for providing sustainable development of enterprises; valuation of investment resources; risk and efficiency calculation of investment projects; Identification of factors that influence the deviation of the actual results of the investment activity from the planned; assessment of the achieving the target indicators after the realization of investment projects as well as assessment of possible reserves to improve the results. One should agree that important factors of investment attractiveness in Ukraine are: low level of corruption, transparent and clearly defined legislative and regulatory frameworks and political stability. When investing, the management of each enterprise is obliged to develop the investment strategy of the enterprise, choose the forms and objects of investment, search for sources of financing, choose investors and participants of the investment process, develop, analyze and evaluate investment projects, control the results of investment activity. The main tasks of management of investment activity of an enterprise should be: maximizing the investment profit; minimizing the investment risk; finding ways to improve investment processes. Influence of the industry features of management of investment activity on the business entity are revealed. By improving information security, strategic planning, evaluation of organization, control, regular monitoring of investment projects and implementation of financial and economic calculations, it is possible to achieve high efficiency of management of the investment activity of the business entity. Having a clear organization of the process of managing the investment activity of the economic entity can be argued about the system of its effective functioning in conditions of decentralization.